Towards the Generalized Criterion for Evaluation of Business Process Model Quality - Kopp, A. M.; Orlovskyi, D. L. (CEUR Workshop Proceedings, 2020)
Business process management has become the most widely-used and reliable approach to organizational management over the last decades. It is also considered as a part of quality management system in an organization. Business process modeling is the core of business process management, which is used for visualization, analysis, and improvement of organizational activities. Moreover, business process modeling plays an important role in the context of business process management maturity of an overall enterprise. Therefore, this paper is focused on the problem of business process model quality evaluation. Existing approaches based on the process modeling guidelines, measures and corresponding thresholds are reviewed, as well as the refined process modeling rules, corresponding quality criteria, the generalized quality criterion, and thresholds for its translation into linguistic values are proposed. The data model and software prototype are developed and the validation results are outlined.
Keywords: business process management; business process model; process model quality; process model metric; quality criteria